Effect of carbohydrate supplementation on hormonal and immune responses of young tennis players - Capitani, C. D.; Gomes, R. V.; Coutts, A. J.; Moreira, A.; Aoki, M. S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The aim of the present investigation was to assess the effect of CHO supplementation on hormonal and immune responses during prolonged tennis match play with well- trained young players (n=12; top 50 in Brazil ranking) in an ecological setting. It was hypothesized that CHO supplementation would attenuate the physiological responses related to a match play. Methods: The study was conducted following a randomized, double-blind, placebo-controlled design in order to determine the influence of a carbohydrate versus placebo beverage ingestion on hormonal and immune responses to 3 h of tennis match. Cortisol , testosterone and immunoglobulin A (IgA) concentrations were assessed from saliva samples collected four times on each testing day [7:00, 9:00 (pre-match), 12:00 (postmatch), 17:00 and on the following morning 7:00]. Salivary steroid hormones and IgA concentration were determined by ELISA kits. Results: Accordingly, to the initial hypothesis, carbohydrate ingestion was associated with lower post-match salivary cortisol (p<0.05). No influence of carbohydrate supplementation on salivary testosterone was observed (p>0.05). IgA response was not affect during both experimental conditions (p>0.05). Conclusion: These data indicate that carbohydrate ingestion during 3 h of competitive tennis match play attenuates salivary cortisol increase as compared to placebo feeding. Previous studies have shown that CHO ingestion during prolonged, high-intensity, intermittent exercise can protect against a decrease in plasma glucose levels that reduces the activation of the hypothalamic-pituitary-adrenal (HPA) axis and blunts cortisol release. On the basis the current findings, it is recommend that players consume CHO to assist in blood glucose regulation and minimize the stress hormones release during extended tennis match play.